LARANGAN KEPEMIMPINAN PEREMPUAN DALAM PERSPEKTIF HADIS - Astuti, Adinda Diah; Eva Arifia; Rizqi Auliya; Kharirotul Badriyah (Aqwal: Journal of Qur'an and Hadis Studies, 2020)
Discourse of women’s leadership is never-ending to discuss. Some Islamic theological considerations has always been a major reason to support equality between men and women. This article presents the textual and contextual analysis of the leadership of women is the public sphere. It is based on textual understanding of the Sunnah pf the Prophet and the opinion of the majority of Muslim scholars poorly stated that the leadership of women is public affairs is prohibited, but is based on contextual underdtanding is not the case with the proviso able to carry out the mandate. Islamic history record’s Aisyah, al-Syifa, and Queen Balqis including a handful of women leader who occupy public office. Therefore, in the understanding of women leadership issues, contextual understanding must first be considere.